Electron ionization and low energy electron attachment to molecules of biological interest. (August 2015) - Śmiałek, M A; Tanzer, K; Neustetter, M; Huber, S; Schürmann, R; Bald, I; Denifl, S
Synopsis: Ethylenediaminetetraacetic acid (EDTA) and 2-amino-2-(hydroxymethyl)-1, 3-propanediol (TRIS) were investigated by electron impact ionization and low energy electron attachment. Both compounds are components of biological buffers and often are used as DNA stabilizers in irradiation studies. hus it is of a great importance to understand their potential interactions with radiation. Our results revealed that at least one of them, EDTA, may influence the experimental outcomes by O − and OH − production upon electron attachment.